Giải thích và hướng dẫn áp dụng các nguyên tắc thiết lập tiêu đề cho bộ tiêu đề chủ đề tiếng Việt - Nguyễn, Hồng Sinh (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Presenting the explanation and guidelines to apply the six rules in establishing titles for the Vietnamese subject headings. The six rules include: Usage and Users, Title establishing based on the materials; United title; Unique title; Identification; Consistency.